DETERMINATION OF HORIZONTAL LOADS ON VERTICAL WALLS OF SILOS ACCORDING TO DIFFERENT STANDARTS - Бібік, М. В.; Мороз, П. С. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The analysis of world standards of determination of pressure of bulk materials on vertical walls of silos is provided in the article. Pressure from the influence of bulk materials is determined for a range of silo constructions in accordance with Ukrainian and Europe standards. The analysis of results is provided. Imperfections and differences of different design standards are indicated. Keywords: silo, storage bunker, Jansen-Canan’s theory.